NURSING GUIDANCE IN THE PHYSIOLOGICAL ADAPTATIONS OF PREGNANCY - Ricardo Saraiva Aguiar; Maria Aparecida Batista de Araújo; Marli Aparecida Costa; Nicoly Aguiar (Universidade Federal do Paraná, 2013)
This study aimed to analyze nursing guidance provided to pregnant women regarding the most frequent clinical complaints during pregnancy. It is a descriptive study with a qualitative approach, undertaken between March and April 2011, with the participation of 14 pregnant women registered in a Primary Health Care Center in Gurupi, in the state of Tocantins. A semi-structured interview script was used and the results being analyzed using content analysis. The principal symptoms mentioned were nausea, vomiting, edema and lower back pain; the guidance provided by the nurse in the pre-natal care for those at low risk was adequate and allowed the pregnant women to understand the symptoms experienced. Interventions relevant to the manifestations were indicated, in spite of the fact that not all the recommended interventions were covered.